Refractoriness of gold concentrates - Arias Arce, Vladimir (2005)
In the extraction and purification of precious metals diverse techniques gravimetric, pyrochemical, hidrochemical, electrochemical are used main to ore sulfides or complex sulfides that contain concealed gold or microscopic gold. The influence of the pyrite presence, copper minerals, that they slow down, they inhibit and /or the transformation metallic gold in solution, they manage to attenuate themselves or to be reduced by means of other necessary treatments that they complement to the cyaniding process, those that can be cycles of roasting, watery leachings with basic acid solutions or under controlled conditions of pressure and temperature, electro oxidation under electrical potential, sequences of ultrasound and by means of the bacterial leaching.